Modified case-based learning as supplement to bedside teaching-why, how and what next? - Mannari, Jyoti G.; Bhende, Punam V.; Ghosh, Sarmishtha (International Journal of Research in Medical Sciences, 2025)
Background: Competency based medical education requires the teaching learning methods and assessment to conform to the framework of competencies. The pandemic disrupted medical education; but led to modifications and innovations in teaching methodologies. We adopted modified CBL for third year part 2 students, alongside bedside teaching to explore its efficacy in terms of improving clinical reasoning, group dynamics, summarizing, presentation and to highlight perceptions of students regarding CBL and its adoption as a regular teaching learning activity. Methods: CBL sessions were taken every afternoon by faculty from department of medicine, trained by department of Health Professions Education; who used real life authentic cases. At the end of each posting, evaluation was planned based on Kirkpatrick hierarchy. Google form, focussed group discussions and content analysis, OSCE stations, bedside case presentation and MCQ based tests were used. Results: Learning assessment tools showed that CBL enhanced learning. Feedback from students revealed that CBL encouraged discussions and critical thinking and through FGDs they suggested the need for advance topic information, more pre-reading time, blending CBLs with lectures when relevant and selecting specific topics to be taught through CBL. Conclusions: Our study demonstrates that modifying CBL-based teaching and including it in clinical postings as a substitute/ supplement to bedside teaching during times when there is lack of clinical material is feasible and effective, as shown by the performance of students in the MCQs. It also appeals to the students and the clinical case scenarios mirror real-world situations, enhance learning and facilitate the clearing of concepts.